A novel method for the general application of measured load spectra to different high-speed train bogie frames based on virtual track irregularity. (July 2022) - Ji, Chengxiang; Sun, Shouguang; Li, Qiang; Wang, Wenjing; Ren, Zunsong; Yang, Guangxue
Highlights: Field load histories of different bogies in coupled operation were measured. A simplified vehicle dynamics model matching the bouncing load was established. The virtual track irregularity was obtained based on the measured load history. The actual load history was accurately predicted based on the VTI and SVDM. Abstract: This paper describes a novel method for the general application of measured load spectra to the bogie frames of different high-speed trains. It is based on virtual track irregularity (VTI), an inversion of the measured load history, combined with a simplified vehicle dynamics model (SVDM). First, the A/B-type bogie frames and their attached components were strain gauged to measure the field load histories in coupled operation under actual operating conditions. Then, a comparison of the measured load spectra and an attempted mutual application of the damage consistency load spectra (DCLS) were conducted. Finally, as an example, the SVDM matching the bouncing load was established, and a complete procedure was proposed for generating the VTI in the time domain. The agreement between the measured and calculated load spectra indicated that the actual load histories acting on the different bogie frames can be accurately predicted based on the VTI and SVDM.